The elements of Malaysian culture based on Seah Kim Joo painting using Erwin Panofky’s Theory - Alias, Izzati; Syed Abu Bakar, Syed Alwi; Omar, Aznan (Universiti Teknologi MARA, Perak, 2025)
This study delves into the identification and analysing of the element of Malaysian culture within the selected paintings of Seah Kim Joo’s titled ‘Malay Kampong’ and ‘Market Scene’. This study employed a qualitative literature review to gather secondary data on cultural characteristics and elements, with a particular focus on identifying features and influences distinctive to the Malaysian context. The study applies Erwin Panofsky’s theory of iconography to identify and analyse elements of Malaysian culture, emphasizing the interpretation of meaning beyond the surface subject matter. Panofsky’s framework consists of three key levels: pre-iconographical description, iconographical analysis, and iconographical interpretation, which together provide a structured way to finding the deeper cultural value hidden in visual representations. Seah Kim Joo's artworks effectively showcase important cultural elements, highlighting their connection to Malaysian culture. The components of culture are categorised into two categories: material culture, which is tangible, and non-material culture, which is intangible. The analysis shows that the two selected artworks include aspects of material culture, such as art, clothing, food, and pastimes, as well as non-material culture, like norms and social institutions. These findings indicate that the artworks accurately capture the essence of Malaysian culture, exhibiting their cultural value and authenticity.